Iron Chelation Property, Antioxidant Activity, and Hepatoprotective Effect of 6-Gingerol-Rich Ginger (Zingiber officinale) Extract in Iron-Loaded Huh7 Cells - Hataichanok Chuljerm; Narisara Paradee; Dabudsawin Katekaew; Panaphat Nantachai; Kornvipa Settakorn; Somdet Srichairatanakool; Pimpisid Koonyosying (Plants, 2023)
Iron is essential for numerous biological processes; however, an iron imbalance can contribute to a number of diseases. An excess of iron can accumulate in the body and subsequently induce the production of reactive oxygen species (ROS), leading to oxidative tissue damage and organ dysfunction. The liver, a major iron storage site, is vulnerable to this iron-induced oxidative damage; however, this issue can be overcome by the chelation of excess iron. This study aimed to investigate the effect of 6-gingerol-rich ginger (Zingiber officinale) extract on iron chelation, antioxidation, and hepatoprotective function in protecting against iron-induced oxidative liver cell injury. In experiments, 6-gingerol was confirmed to be a main bioactive component of the ginger extract and possessed free radical scavenging activity, decreasing ABTS•+ and DPPH• radical levels, and inhibiting AAPH-induced red blood cell hemolysis. Interestingly, the extract significantly reduced the levels of labile cellular iron (LCI), intracellular ROS, and lipid peroxidation products (TBARS) in iron-loaded human hepatoma (Huh7) cells. In conclusion, this work highlights the iron chelation property of 6-gingerol-rich ginger extract and its antioxidant activity, which could potentially protect the liver from iron-induced oxidative tissue damage.